Entrepreneurship Training For Processing Local Food Based Products For Food Msmes at Grobogan Food Technopark - Qodriyati, Tri 'Ulya; Ach. Rasyad, Ach. Rasyad; Supriyono, Supriyono (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2024)
Entrepreneurship training is a strategic effort to increase the capacity and competitiveness of Usaha Mikro, Kecil, dan Menengah (UMKM) in the food sector. This research aims to examine the effectiveness of entrepreneurship training for processing local food-based products held at the Technopark Pangan Grobogan. The research method used is a qualitative method with a grounded theory type involving observation, in-depth interviews and document analysis. This training is designed to provide knowledge and skills to food UMKM in processing local food ingredients into high added value products. The training material covers food processing techniques, business management, marketing, as well as legal aspects and product certification. Training participants demonstrated significant improvements in technical understanding and ability after attending the training program. The research results show that this training not only improved the technical skills of the participants but also strengthened their business networks through collaboration and partnerships established during the training. Challenges faced include limited access to modern processing technology and difficulties in marketing products more widely. However, the positive impact of this training can be seen in improving product quality, increasing sales and diversifying products produced by food UMKM. This research concludes that entrepreneurship training in processing local food- based products has great potential to support the development of food UMKM in the Technopark Pangan Grobogan. Recommendations are given for training organizers to continue to update training materials in accordance with technological and market developments, as well as provide ongoing support for participants to overcome the challenges they face.Keywords: Entrepreneurship Training, small and medium and intrerprise local food processing, Technopark Pangan Grobogan.